О новых реализациях групп Пуанкаре Р(1,2),Р(2,2) - Жданов, Р.З.; Лагно, В.И. (Український математичний журнал, 2000)
Проведено класифікацію реалізацій груп Пуанкаре Р(1,2),Р(2,2) в класі локальних груп Лі перетворень. Отримано ряд нових реалізацій алгебр Лі інфінітезимальних операторів цих груп. We classify realizations of the Poincare groups P (1, 2) and P (2, 2) in the class of local Lie groups of transformations and obtain new realizations of the Lie algebras of infinitesimal operators of these groups.